d- and f -metal alkoxy-tethered N-heterocyclic carbene complexes - Fyfe, Andrew Alston (The University of Edinburgh, 2016)
Chapter one is an introduction, outlining the structure and bonding of N-heterocyclic carbenes (NHCs). It then goes on to give examples of f -metal NHC complexes and describes any reactivity or catalytic activity. Chapter two describes the synthesis of the transition metal NHC complexes [Fe (LMes)2] 3 and [Co(LMes)2] 4 (LMes = OCMe2 CH2(1-C{NCH2CH2NMes})). The heterobimetallic complexes [(LMes)Fe(μ-LMes)U(μ-{N(SiMe3)Si(Me)2CH2})(N(Si Me3)2)2] 5 and [(LMes)Co(μ-LMes)U(μ-{N(SiMe3)Si(Me)2CH2})(N(SiMe3)2)2] 6 were prepared from the reaction between [({Me3Si}2N)2U(NSiMe3SiMe2CH2)] and 3 or 4, respectively. Complex 5 was also synthesised by the reaction between 3 and [U(N{SiMe3}2)2]. The diamagnetic analogue [(LMes)Zn(μ-LMes)Th(μ-{N(SiMe3)Si (Me)2CH2})(N(SiMe3)2)2] 9 was prepared from the reaction between [Zn(LMes)2] and [({SiMe3}2N)2Th(NSiMe3SiMe2CH2)]. The reactivity of 5 is discussed. When 5 was reacted with 2,6-dimethylphenyl isocyanide, [({SiMe3}2N)2U{N(SiMe3)Si(Me2)C(CH2)N(2,6−Me−C6H3)}] 8 was isolated. The reaction with CO resulted in the formation of [({Me3Si}2N)2U{N(SiMe3) Si(Me2)C(CH2)CO}]. 5 showed no reactivity with azides, boranes or m-chloroperbenzoic acid and decomposed when exposed to H2, CO2 or KC8. The reaction between 6 and 2,6-di-tert-butylphenol formed the previously reported monometallic complex [({SiMe3}2N)2U(OC6H3tBu2)]. The serendipitous synthesis of the iron ate complex [Na(Fe{LMes}2)2]+ [Fe(ArO)3]– 10 (Ar = 2,6-tBu-C6H3) is also described. Chapter three describes the synthesis of the aryloxide complexes [HC(3-tBu-5-Me- C6H2OH)(3-tBu-5-Me-C6H2O)μ-(3-tBu-5-Me-C6H2O)Co(THF)]2 11 and [HC(3- tBu-5-Me-C6H2OH)(3-tBu-5-Me-C6H2O)μ-(3-tBu-5-Me-C6H2O)Zn(THF)n] 13. Treatment of 11 with pyridine N-oxide resulted in the formation of the pyridine-Noxide adduct [HC(3-tBu-5-Me-C6H2OH)(3-tBu-5-Me-C6H2O)μ-(3-tBu-5-Me-C6H2 O)Co(C5H5NO)]2 12. When 11 was treated with [({Me3Si}2N)2U(NSiMe3SiMe2C H2)], no reaction occured at room temperature but at 80◦C decomposition occured. When 11 was treated with [(NH4)2Ce(NO3)6] the protonated proligand HC(3-tBu- 5-Me-C6H2OH)3 reformed. The reactivity of 11 with [({Me3Si}2N)Ce(LiPr)2] is also discussed. Chapter three also discusses the preparation of the heterobimetallic complex [HC(3- tBu-5-Me-C6H2O)2-μ-(3-tBu-5-Me-C6H2O)KCo]2 14 and the salt-elimination chemistry of the complex. The preparation of [HC(3-tBu-5-Me-C6H2O)2-μ-(3-tBu-5- Me-C6H2O)KZn]2 15 is also outlined. Chapter four discusses the reactivity of [Ce(LiPr)3] (Li Pr =OCMe2CH2(1-C{NCHC HNiPr})) in C-H and N-H activation and as a catalyst for organic reactions. [Ce(LiPr)3] displayed no C-H activation chemistry with RC−−−CH (R = SiMe3, Ph, tBu), diphenyl acetone, indene or fluorene. [Ce(LiPr)3] also showed no N-H activation chemistry with pyrrole or indole, nor did it react with the lignin model compound PhOCH2Ph. When treated with an excess of benzyl chloride, [Ce(LiPr)3] underwent ligand decomposition to form the acylazolium chloride [(C6H5C(O))OCMe2CH2(1-C(C6H5C (O)){NCHCHNiPr})]Cl 18 and CeCl3. When [Ce(LiPr)3] was added to a mixture of benzaldehyde and benzyl chloride, as a coupling catalyst, the complex decomposed. [Ce(LiPr)4] was tested as a catalyst from the benzoin condensation and for the coupling of benzalehyde and benzyl chloride, however, it resulted in the decomposition of [Ce(LiPr)4]. Chapter four also outlines the catalytic activity of 3. The complex showed no reactivity as a hydrogenation catalyst towards alkenes, aldehydes or ketones but did display reactivity as a hydroboration catalyst for alkenes, aldehydes or ketones. Chapter five presents the conclusions for chapters two to four. The final chapter contains the experimental details from the previous chapters.
Keywords: actinide; N-heterocyclic carbene; NHC; bimetallic; heterobimetallic; C-H activation